Performance Efficiency of the Indonesian Banking - Lule, Benny (JBE (Journal of Business and Economics), 2009)
This paper aims to measure and analyze the performance efficiency of the Indonesian banking listed in IDX for LQ 45 during period 2003 – 2007. The study uses Output-Oriented Malmquist Productivity Index (DEA approach) to analyze 35 panel data composed of 7 banks and 5 year periods. The findings show that the Indonesian banking is productive and efficient as a whole.  There are positive growth productivity and efficiency rate as much as 5.1 percent and 2.4 percent, respectively. However, the findings show that 29 percent of the banks are non-productive and 43 percent is inefficient ones.